2023
DOI: 10.26714/mki.6.1.2023.25-32
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Contributing to Treatment Success among Tuberculosis Patients: Cross-Sectional Study in Semarang, Indonesia

Abstract: The success rate of TB treatment in Semarang City in 2021 will reach 81.15%. Patients recovered reached 20.20%. Complete Treatment reached 60.95%. Failed treatment 0.15%. Patients Died reached 5.96%. Treatment dropout (lost to follow-up) reached 12.43%. Not evaluated/moved reached 0.31%. This study aims to identify the factors that contribute to the success of TB treatment. This study used secondary data sourced from the Semarang City Tuberculosis Information System (SITB) which was recorded regularly during 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…This study also found Patients treated for TB at primary healthcare 1.2 had a greater success rate in their therapy compared to those treated at the hospital. Research in Semarang, Indonesia, found that patients treated at Puskesmas were 3.7 times more successful than those treated in the hospital (p = 0.000) (Rakhmawati et al, 2023). In 2015, the successful treatment rate for tuberculosis at 30 primary health care facilities in Bekasi City was 85.2%.…”
Section: Discussionmentioning
confidence: 98%
“…This study also found Patients treated for TB at primary healthcare 1.2 had a greater success rate in their therapy compared to those treated at the hospital. Research in Semarang, Indonesia, found that patients treated at Puskesmas were 3.7 times more successful than those treated in the hospital (p = 0.000) (Rakhmawati et al, 2023). In 2015, the successful treatment rate for tuberculosis at 30 primary health care facilities in Bekasi City was 85.2%.…”
Section: Discussionmentioning
confidence: 98%